Aspectos jurídicos e econômicos da reparação dos danos causados às vítimas dos crimes contra a honra praticados na internet - Silva, Ricardo José de Medeiros e (2010)
The humankind as a whole goes through a quick and continuous process of change in the social, economic and politic spheres. The world reality has already transformed itself. What once in the past looked lame and took decades to change, now changes with a single click of a computer keyboard. We live nowadays a constant process of evolution of the world society where cultural and economic globalization makes its path into the virtual world of the Internet. The Internet phenomenon, called Web of webs, already impacts the human universe in unimaginable proportions through a digital convergence process where man interacts with another man, each time and more through an infinite virtual space that respects no cultural differences, geographical limits or State Sovereignties. The economic and cultural globalization of the societies also requires the globalization of the juridical thought as a whole in order to find efficient mechanisms and apply legal norms that last and endure beyond the territorial principles, especially when it concerns to Penal Law and Economic Law. In these terms, the present work intended to analyze, under the Economic Law view, the circumstances that involve the legal reparation of the victims from the crimes against the honor perpetrated on the Internet. From the law operator´s point of view the difficulties are enormous, even because Internet is a world phenomenon, homogeneous, countrywide and landless, with no spatial or geographical delimitations, and with immaterial consistency. It is a universe which has not been predicted by the traditional historic cultural reality of Law. The three-dimensional Theory that brought the fact, the value and the norm, now faces the challenge of dealing with a social reality far different from what existed decades ago. The Internet phenomenon is still little known among us, but Law has to adapt as fast as possible to this new Era of virtuality. It is from this adjustment capacity and projection of valid and efficient legal norms to the virtual universe of the Web of webs that emerges the necessary juridical safety to the national judicial systems of each country in the world. This work aims to contribute uniquely with the discussion and the possible and viable solutions of questions related to the economic consequences that come up with the practice of crimes against the honor of people through the World Wide Web. The Internet, as we know it today, represents the technology of freedom, and this is good. What brings up such discussions and what one tries to avoid is the risk of the ineffectiveness of Law towards the illicit conducts and the old and new outlaw behaviors that currently occur in its virtual space that if not hold back, cause economic and social injuries witch bring discomfort and juridical insecurity to millions of people.